Vocational extension strategy aimed at the professional training of dental careers students - Judith Áucar López; Maitee Lajes Ugarte (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2021)
Background: permanence in university careers continues to present shortcomings, a fact that also reaches Cuban higher medical education. This problem, in direct relation to vocational guidance, can be mitigated with actions such as the promotion of university outreach activities to school populations, which in turn allow the integral development of university students. Objective: to implement a vocational extension strategy oriented to the professional training of stomatological careers students. Methods: an intervention research was carried out at the Camagüey University of Medical Sciences, Cuba, between January 2015 and January 2020. Primary school students, their parents or guardians, and assistant students of the Stomatology and of Technology in Stomatological Attention, directed by assistant professors of the Faculty of Stomatology participated. The level of information about the dental profession, oral-hygiene habits of infants and oral hygiene; degree of satisfaction of the participants; and opinions of the students were analyzed. Results: female sex predominated among the schoolchildren enrolled in the group of interest. At the end of the intervention, an adequate level of information (98.1%) and oral hygiene (98.1%) were evidenced, unlike what was initially observed. Future stomatologists and technologists recognized the personal and professional enrichment provided by the actions developed. Conclusion: the activities of vocational guidance, promotion and prevention of oral health, executed as part of the extension strategy, contributed to the development of interprofessional education and professional training of the university students involved.